Musashi Proteins as Prognostic Biomarkers: Role in Leukemic Cancer and Stem Cells Growth - Baig, Muhammad Haris; Umaru, Isaac John (African Journal of Biochemistry and Molecular Biology Research, 2025)
Leukemia stem cell's (LSC) ability to self-renew and survive depends on the RNA-binding regulators known as Musashi proteins (MSI1 and MSI2). By stabilizing the mRNAs of key oncogenes like HOXA9 and MYC, MSI2 encourages leukemia growth and treatment resistance, especially in acute myeloid leukemia (AML). On the other hand, MSI1 enhances Notch1 signaling, which helps explain the traits of cancer stem cells in leukemia and solid tumors. Since dysregulation of these proteins is linked to recurrence, treatment resistance, and poor prognosis, they are crucial therapeutic targets. Preclinical research indicates that treatments targeting MSI proteins have potential results. Small-molecule inhibitors and RNA-based methods are being developed to disrupt MSI RNA connections, lowering LSC self-renewal and enhancing chemotherapeutic responses. Inhibiting MSI2 can reduce key pathways such as β-catenin and STAT3, improving therapeutic success in AML. CRISPR-Cas9 technology has also shown promise in overcoming therapeutic resistance by deactivating MSI2.